Dr J. [Jerzego] Jurkowa Ex Libris / Dolatowski. - Dolatowski, Zbigniew (1927-2001) (1965)
Napis u góry: Dr J. Jurkowa, u dołu: Ex Libris. Sygn. aut. w obrębie kompoz., pod wyobrażeniem autograf aut. i data.